Designing C0-KIDS (Color and Number) Application for Intellectual Disabilities Students - Rosida, Fatia; Fikri, A. Kanzul; Bahtiar, Yuyun; Ma’arif, Iin Baroroh; Fitriani, Rohmatul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Education is the most important aspect of life, every Indonesian has an entitlement to it and should always pursue more education. In this research, the researcher designed an interactive media application to help with intellectual disabilities in English learning process. The media application was focused on listening skills namely the C0-KIDS application. The ADDIE model, which comprised five steps (analysis, design, development, implementation, and evaluation), was adapted for use in this study using the Research and Development (R&D) technique. Students with intellectual disabilities from SMPLB Tunas Harapana I Tembelang participated in this study. The researcher obtained the research's outcome from those procedures. 1) The material validation score was 92 (also in the Very Good Category), and the media validation result was 93 (also in the Very Good Category). Based on the findings, the researcher draws the conclusion that students with intellectual impairments should utilize the C0-KIDS program to learn English, particularly in the area of listening skills.